Effectiveness of Using the School Budget Work Plan Application in Reporting Accountability of School Operational Assistance Funds - Rena Muliasari; Muhamad Husein Maruapey; Oetje Subagdja (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
Implementing the school budget work plan application is closely related to implementing School Operational Assistance Funds in education.. This research aims to determine the effectiveness of the School Budget Work Plan Application in reporting accountability for School Operational Assistance funds at the West Java Provincial Education Service. The research method uses a qualitative approach with descriptive analysis. Research informants using a purposive sampling technique. Data collection techniques use observation and interviews based on primary and secondary data, then credibility, transferability, dependability, and confirmability tests are carried out to validate the data. The research shows that the School Operational Assistance funds management through the School Budget Work Plan Application system can be effective based on the concept of effectiveness theory. This is demonstrated by an understanding of the School Operational Assistance funds program so that successful management of School Operational Assistance funds is achieved in an appropriate, timely manner, achieving goals and achieving absolute truth through technical guidelines at the West Java Provincial Education Office. Thus, the novelty of this research is to look at the effectiveness of transitioning the management and reporting of school operational assistance funds through the School Budget Work Plan Application system so that it can guarantee accountability in reporting funds.